Preserving fertility in patients undergoing treatment for breast cancer: current perspectives - Moffat R (Dove Medical Press, 2014)
Rebecca Moffat,1 Uwe Güth2 1Women’s Hospital, Clinic for Gynecologic Endocrinology and Reproductive Medicine, University Hospital Basel, Basel, 2Department of Gynecology and Obstetrics, Breast Center, SenoSuisse, Cantonal Hospital Winterthur, Winterthur, Switzerland Abstract: Invasive breast cancer (BC) is the most frequent cancer of young women. Considering the trend toward postponing childbearing until the later reproductive years, the number of childless women at diagnosis of BC will continue to increase. The American Society of Clinical Oncology and the American Society for Reproductive Medicine have recommended that the impact of cancer treatments on fertility should be addressed with all cancer patients of reproductive age and that options for fertility preservation, such as cryopreservation of embryos and oocytes, ovarian tissue, in vitro maturation of immature oocytes, and ovarian suppression with gonadotropin-releasing hormone analogs, should be discussed routinely. To optimally counsel patients on how to best weigh the risks and benefits of fertility preservation, both the health care provider and the patient must know about the options, their risks, and their likelihood of success. The aim of this review is to summarize current knowledge on fertility preservation options for young BC patients, surrogates of ovarian function, psychosocial aspects of infertility after cancer treatment, women’s attitudes towards childbearing after cancer treatment, and health care providers’ attitudes towards fertility preservation. Keywords: breast cancer, fertility preservation, oncofertility, chemotherapy